Interest and Habit in Reading English Literature of The Forth Semester Nursing Students at Stikes Eka Harap Palangka Raya - Nata, Ipan Dwi; Chintia Monica Roliani; Vina Agustina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The advancement of information and technology in health requires health science students to continuously adapt themselves globally and internationally by improving their access to various literature, especially those written in English. This study intended to give a description of students’ reading interest and habit, especially toward English written literature. This study was carried out by a descriptive quantitative method. The respondents were 175 students who were selected by a purposive sampling technique. The research findings showed that students’ interest and habit towards English-written literature were low. It could be derived from the majority (50.9%) “like” to read. Unfortunattely, only 30,9% who “like” to read English Literature, 45,1% stated “so-so” and 24% “dislike” reading English- written literature. In addition, as much as 67.9% respondents spent less than an hour per day to read English-written literature. Therefore, some integrative efforts to improve students’ reading interest and to build students reading habit are needed, for instance, by integrating literacy program into students’ learning activities of all courses.